Dynamic Wetting Behavior of Vibrated Droplets on a Micropillared Surface - Zhi-hai Jia; Wei Lei; Hui-nan Yang; Gang Wang (Advances in Materials Science and Engineering)
The dynamical wetting behavior has been observed under vertical vibration of a water droplet placed on a micropillared surface. The wetting transition takes place under the different processes. In compression process, the droplet is transited from Cassie state to Wenzel state. The droplet undergoes a Wenzel-Cassie wetting transition in restoring process and the droplet bounces off from the surface in bouncing process. Meanwhile, the wetting and dewetting models during vibration are proposed. The wetting transition is confirmed by the model calculation. This study has potential to be used to control the wetting state.